Racial/Ethnic Disparities in Revascularization for Limb Salvage: An Analysis of the National Surgical Quality Improvement Program Database. (July 2014) - Hughes, Kakra; Boyd, Christopher; Oyetunji, Tolulope; Tran, Daniel; Chang, David; Rose, David; Siram, Suryanarayan; Cornwell, Edward; Obisesan, Thomas
Introduction: Previous reports have suggested that black patients have a higher rate of major lower extremity amputation and a lower rate of revascularization for limb salvage when compared to white patients. Objective: We undertook this study to determine the extent of this ethnic disparity in recent years and to evaluate whether the widespread adoption of endovascular techniques has had an impact on this disparity. Methods: The American College of Surgeons' National Surgical Quality Improvement Program (NSQIP) database was queried to identify all patients who had undergone an above- or below-knee amputation as well as all patients who had undergone an open or endovascular revascularization procedure for critical limb ischemia for the years 2005 to 2006. Patient demographics and 30-day outcomes were recorded, and comparisons were made among the different ethnic groups. Results: There were 1568 patients identified in the NSQIP database as having undergone a major lower extremity amputation in 2005 and 2006. Of these patients, 54% were white, 29% black, 8% Hispanic, and 0.7% Asian. Eight percent of patients did not have identifying ethnic data. The group undergoing amputation was primarily male (61%) with a mean age of 65. Median length of stay was 11 days, and 30-day mortality was 9% following amputation. During this same time period, 4191 patients underwent an open surgical procedure and 569 patients underwent an endovascular procedure for the purposes of limb salvage. Of those patients undergoing an open procedure, 74% were white, 12% black, 4% Hispanic, 0.4% Asian, and 10% did not have identifying ethnic data. Open surgical patients were primarily male (63%) with a mean age of 66. Median length of stay was 6 days, and 30-day mortality was 3.3%. Of those patients undergoing an endovascular procedure, 79% were white, 10% black, 2% Hispanic, 1% Asian, and 8% did not have identifying ethnic data. The endovascular group was also primarily male (61%) with a mean age of 68. Median length of stay was 5 days, and 30-day mortality was 4%. Conclusion: There remains a significant ethnic disparity in limb-salvage revascularization. Blacks comprise 29% of patients undergoing a major lower extremity amputation, but only 12% of those undergoing an open surgical procedure and 10% of those undergoing an endovascular procedure for limb salvage. The widespread adoption of endovascular revascularization techniques appears not to have had much impact on this disparity.